Understanding the Interaction Between Prostaglandins and Toll-Like Receptors in Nicotine-Induced Rectal Tumor in Animals - Wang Peng; Li Changlu; Seshadri Sriram; Seshadri Sriram; Jiangang Liu (Turkish Journal of Gastroenterology, 2022)
Background: In the present study, we tried to understand the crosstalk between prostaglandins-COX-mediated rectal tumors and toll- like receptors in rats. Methods: The tumor was induced using nicotine (100 μL/mL). Following the induction, the serum and rectal tissue were analyzed for Lipo-polysaccharides (LPS) and prostaglandin E2 in serum, and tissue expression of inflammatory mediators like TLR2,4, NFkB; cancer markers like Matrix metalloproteases 2 (MMP2), 9 and Cyclo-oxygenases 2 (COX-2) were estimated. The gut microflora analysis was carried out using the fresh fecal samples of both the study groups. Results: In nicotine-induced group, there was a significant alteration in the gut microflora toward high Gram-negative strains and a decline in Gram-positive populations. All the inflammatory as well as cancer prognostic markers were significantly increased in the tumor-induced animals. Conclusion: From the present study, it could be concluded that nicotine significantly induced rectal cancer in the mice model by modu- lating gut microflora and increasing COX-2 and prostaglandin E2 levels. Cite this article as: Peng W, Changlu L, Sriram S, Liu J. Understanding the interaction between prostaglandins and toll-like receptors in nicotine-induced rectal tumor in animals. Turk J Gastroenterol. 2022;33(6):491-496.